(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Introduction and Aim: Early childhood is the most important period for gaining basic movement skills and improving physical fitness parameters. Physical fitness level is a determinant of health an early age. Influencing one of the physical fitness parameters related to health or performance directly affects physical fitness. The aim of this study was to evaluate the morphological and motor development characteristics of children in the 12-week movement education program, and a research for 7-9 years old childhood was discussed.Material and Methods: A total of 116 male students aged 7-9 participated in the study. A 12-week movement training program was applied to the students participating in the research. Before starting this program, in order to measure morphological features as a pre-test, body fat ratio, height, body weight, body mass index (BMI), head circumference, neck circumference, chest circumference, abdominal circumference, Hip circumference measurements. On the other hand flexibility, horizontal jump, vertical jumping, push-ups, sit-ups, touching the discs, 10 meters sprint, Balance flamingo measurements were taken as a performance characteristics. The same measurements were taken again as a post-test after the 12-week movement training program was over. The data of the research were analyzed in IBM SPSS 25.0 program. The mean and standard deviation statistics of the data were calculated. The "Shapiro-Wilk" test was used to determine whether the data showed normal distribution, and because all variables showed normal distribution, the Repeated Measures ANOVA (intra-group and intergroup comparison) test was performed and the level of significance was stated as P<0.001.Results: When the morphological characteristics were evaluated, there was a significant difference in body weight and body fat percentage within the group, while no significant difference was found in other tests. In the comparison between the groups, a significant difference was found in all tests except body fat percentage. While a significant difference was detected in all tests within the group in performance tests, no significant difference was found between the groups in flexibility, push-ups, sit-ups and sprint values.Conclusion: 12-week movement-based exercise provided improvements in children's motor development and morphological features. Movement education is important for children's morphological characteristics and motor development.